RELATIONSHIP OF DISCIPLINE LEARNING, SELF CONFIDENCE AND FRIENDS WITH PEOPLE OF STUDENTS MATHEMATICS LEARNING OUTCOME - Ismawanti Ismawanti; Harina Fitriyani (Universitas Ahmad Dahlan, 2018)
Low student learning outcomes associated with many factors. Learning discipline, students' self-confidence, and peers are some of the factors possibly related to learning outcomes. This research aims to determine the presence or absence of positive and significant relationships between learning discipline, student's self-confidence, and peers with Mathematics Learning Outcomes in Students Class VIII of SMP Negeri 1 Srandakan District Bantul in Odd Semester Academic Year of 2016/2017. The population in this research was the students of VIII SMP Negeri 1 Srandakan District Bantul in odd semester academic year of 2016/2017, consisted of class VIII A, VIII B, VIII C, VIII D, VIII E, and VIII F, totaling 184 students. Samples were taken from VIII E as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of learning discipline, the student's self-confidence, and peers and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, a test of linearity, and independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between learning discipline, student's self- confidence, and peers with mathematics learning outcomes in students class VIII of SMP Negeri 1 Srandakan District Bantul in odd semester Academic Year of 2016/2017. It is showed by Fcount Â Ftable is Â with R = 0,5649 and R2 = 0,3191 with ,with RC ,RC Â and RC , EC , EC and EC .